Hidden in plain sight [large type] - Archer, Jeffrey, 1940- (Archer, Jeffrey, 1940- William Warwick novels, 2020)
"William Warwick, along with the rest of his team, have been reassigned to the drugs squad. They are immediately tasked with apprehending Khalil Rashidi, a notorious drug dealer, who operates his extensive network out of London. As the investigation progresses, William runs into enemies old and new: Adrian Heath, from his school days, now a street dealer; and financier Miles Faulkner, who makes a mistake that could finally see him put behind bars. As William's team closes the net around a criminal network like none they have ever faced before, he devises a trap they would never expect, one that is hidden in plain sight"--Page 4 of cover.